Hydrogen oxidation reaction: Evidences of different electrocatalytic activity between α and β Pd-H - Rau, Maria Sol (2008)
The hydrogen oxidation reaction (hor) was studied in steady state conditions on a palladium thin film electrode supported on a gold rotating disc. The electrode surface was characterized by cyclic voltammetry and SEM observation. The hydrogen absorption process was analysed by open circuit potential decay in an acid solution saturated with hydrogen and the kinetic measurements were carried out potentiostatically in the same solution. The results obtained show a marked change on the dependence of the current density on overpotential due to the transition between the α and β phases of the Pd-H system. These results were correlated with appropriate kinetic expressions and the corresponding electrocatalytic activity of both phases was estimated.